A cowboy Christmas carol - Curtis, Melinda (Romance fiction writer) (Curtis, Melinda (Romance fiction writer). Cowboy Academy., 2023)
Rodeo roper Ryan Oakley may hate Christmas, but he still needs a miracle. Unfortunately, the only person who sells top-notch competition horses is Jo Pierce, his former high school nemesis. Now Ryan's making the single mom a bargain: he'll set her up with his twin brother, her longtime crush. It's the perfect holiday plan...until the no-nonsense working cowgirl ends up lassoing his heart instead.